Application of an HPLC method for the quality control of vitamin C content in foods for infants - Silva, M.A. (2017)
Vitamin C is an important water-soluble vitamin that humans are not able to synthesize, so it needs to be provided by the diet. Babies less than 1 year usually do not eat foods naturally rich in vitamin C, so the main sources are breast milk and/or infant formulas. Regulation (EU) No. 609/2013, Commission Delegated Regulation (EU) No. 2016/127 and Ministério da Agricultura, do Desenvolvimento Rural e das Pescas (2008) establishes compositional and information requirements for food intended for infants and young children [1-3]. Adequate intake of vitamin C is very important to assure children’s good health and development, so it is crucial to evaluate vitamin C content in this type of foods. The aim of this study was to validate a high-performance liquid chromatography (HPLC) method for the quality control of vitamin C content in infant foods (2 infant formulae (IF), 2 follow-on formulae (FF), 2 processed cereal-based foods (PCF) and 2 baby foods (BF)). In 2016, the infant foods were collected from major supermarket chains and parapharmacies in the region of Lisbon (Portugal). Two of the acquired samples were already ready-to-use, while the remaining samples were prepared according to manufacturer’s instructions. Separation and quantification of vitamin C was carried out on an Alliance 2695 HPLC system, with diode array detection (DAD), using a SynergiTM Hydro-RP analytical column (150 x 4.6 mm I.D., 4.0 μm particle size). Samples were monitored at 245 nm. The HPLC-DAD analytical method was validated for selectivity, linearity, LOD, LOQ, precision and accuracy, using an infant formula. Calibration curves were linear over the range 1-100 µg/mL. The achieved LOD and LOQ were 0.026 and 0.086 µg/mL, respectively. Vitamin C content in the analysed samples ranged from 1.5 ± 0.01 to 178 ± 1.01 mg/100 g for BF1 and PCF2, respectively. The developed method is rapid, specific, precise and accurate, for the quantification of vitamin C in different categories of foods for infants and young children, showing satisfactory data for all the tested parameters. Since this type of food products are very important for such young and vulnerable consumers, regulation and assurance of an adequate intake of essential nutrients, like vitamin C, is extremely important for a healthy development. References: [1] European Parliament/Council of the European Union. (2013). Regulation (EU) No 609/2013 of the European Parliament and of the Council of 12 June 2013 on food intended for infants and young children, food for special medical purposes, and total diet replacement for weight control. Official Journal of the European Union, L181, 35-56. [2] European Commission. (2016). Commission Delegated Regulation (EU) 2016/127 of 25 September 2015 supplementing Regulation (EU) No 609/2013 of the European Parliament and of the Council as regards the specific compositional and information requirements for infant formula and follow-on formula. Official Journal of the European Union, L25, 1-29. [3] Ministério da Agricultura, do Desenvolvimento Rural e das Pescas (2008). Decreto-Lei n.º 53/2008 de 25 de Março. Diário da República, 1ª série - Nº 59, 1667-1674.